On Elliptic Equations in Orlicz Spaces Involving Natural Growth Term and Measure Data. (15th October 2012) - Kbiri Alaoui, Mohammed
Abstract : The paper deals with the existence of solutions of elliptic equations in the framework of Orlicz spaces with right-hand side measure and natural growth term.